Iso-lating optimal automated external defibrillator signage: An international survey - Brandon Stretton; Gregory Page; Joshua Kovoor; Ammar Zaka; Aashray Gupta; Stephen Bacchi; Anjalee Amarasekera; Anoja Gunaratne; Aravinda Thiagalingam; Gopal Sivagangabalan; Pramesh Kovoor (Resuscitation Plus)
Introduction: This study investigated the public’s preference to a recognisable and meaningful signage for Automated External Defibrillators (AEDs) in alignment with ISO 7010 standards, aiming to identify improvements for better public awareness and response during out-of-hospital cardiac arrests (OHCA). Methods: A survey was administered via SurveyMonkey® and Heart of the Nation’s social media. The survey evaluated recognition of ISO signage colors and AED symbols, and preferences for alternative AED signs. Baseline data including geographic location, industry employment, and first aid training were collected. Results: A total of 935 responses were received (Heart of the Nation’s social media (n = 244) Survey Monkey’s (paid, and independent of Heart of the Nation, n = 691). There were 511 from the US and Canada (54.65 %), 222 from the UK and Europe (23.76 %), 133 from the Asia Pacific (14.22 %), 6 from South America (0.64 %), 2 from the Middle East (0.21 %), and 61 from other territories (6.53 %). Among participants, 455 (48.66 %) were first aid trained. The healthcare sector was the most common employment (n = 155, 16.58 %). Only 187 (20 %) participants correctly identified the ISO AED sign. The preferred sign was a yellow sign with a red heart and blue font, chosen by 252 (27 %) participants. Conclusion: Current ISO 7010 AED signage is not widely recognised, and is only correctly interpreted by a small percentage of the public. The study suggests a need for more intuitive and visually distinct signage, such as the preferred yellow sign, to improve visibility and understanding, thereby enhancing AED accessibility and usage in OHCA.